2008
DOI: 10.1523/jneurosci.1106-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Predictive and Postdictive Switching Mechanisms for Internal Models

Abstract: Switching of sensorimotor tasks may be classified into predictive switching based on contextual information and postdictive switching based on the error between sensorimotor feedback and predictions. We used functional neuroimaging to study the brain regions involved in each type of switching of internal models for visuomotor rotations (clockwise and counterclockwise rotations of visual feedback). The color of a cue presented before movement initiation corresponded to direction of rotation of the feedback in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 65 publications
4
48
0
Order By: Relevance
“…This is consistent with our behavioral (Imamizu, Sugimoto et al, 2007) and fMRI (Imamizu & Kawato, 2008) studies indicating the two independent switching mechanisms.…”
Section: Predictive Switching Of Internal Modelssupporting
confidence: 93%
See 1 more Smart Citation
“…This is consistent with our behavioral (Imamizu, Sugimoto et al, 2007) and fMRI (Imamizu & Kawato, 2008) studies indicating the two independent switching mechanisms.…”
Section: Predictive Switching Of Internal Modelssupporting
confidence: 93%
“…In our new experiment, discrete pointing movements and event-related fMRI were used to separate activity related to the presentation of the cognitive cue from that related to sensorimotor feedback (Imamizu & Kawato, 2008). The task for subjects followed that in our behavioral study, and subjects suYciently learned the 40° CW and 40° CCW visuomotor rotations before scanning of brain activity.…”
Section: Predictive Switching Of Internal Modelsmentioning
confidence: 99%
“…This result supports the idea that during learning not an existing model of the complete body plus the current task is adapted-or even newly learnedbut only an additional model of the object or the associated movement dynamics is constructed. Additional support comes from Davidson and Wolpert (2004) and more and more evidence is emerging, favouring a modular organisation of internal models (Imamizu and Kawato 2008;Ghahramani and Wolpert 1997;Krakauer et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that explicit knowledge not only supports the switching between two opposite rotations, but also enhances the long-term development of usually incompatible internal models. If explicit knowledge addresses interference by reducing interactions of incompatible internal models, other cognitive aspects could also play a relevant role, executive functions in particular: Switching of sensorimotor discordances activates the prefrontal cortex (Girgenrath et al 2008;Imamizu and Kawato 2008), which is typically associated with executive functions (Anderson et al 2008;Smith and Jonides 1999). Therefore, the present study also tested whether executive functions predict the amount of interference between two subsequent adaptations.…”
Section: Introductionmentioning
confidence: 90%
“…Seidler et al (2012) described a functional overlap of neural activity between sensorimotor adaptation and a working memory task in the right dorsolateral prefrontal cortex and bilateral inferior parietal lobule. Girgenrath et al (2008) as well as Imamizu and Kawato (2008) reported that the switching of sensorimotor discordances activates the prefrontal cortex and, depending on the task, either the superior or inferior parietal cortex. These neuronal activities support the assumption of an involvement of executive functions in visuomotor adaptation.…”
Section: Role Of Executive Functionsmentioning
confidence: 96%